Ionic Field Screening in MAPbBr3 Crystals Revealed from Remnant Sensitivity in X‑ray Detection - Alvarez, Agustin O.; Lédée, Ferdinand; García-Batlle, Marisé; López-Varo, Pilar; Gros-Daillon, Eric; Guillén, Javier Mayén; Verilhac, Jean-Marie; Lemercier, Thibault; Zaccaro, Julien; Marsal, Lluis F.; Garcia-Belmonte, Germà; Almora, Osbel (ACS Physical Chemistry Au, 2023)
Research on metal halide perovskites as absorbers for X-ray detection is an attractive subject due to the optimal optoelectronic properties of these materials for high-sensitivity applications. However, the contact degradation and the long-term instability of the current limit the performance of the devices, in close causality with the dual electronic-ionic conductivity of these perovskites. Herein, millimeter-thick methylammonium-lead bromide (MAPbBr3) single and polycrystalline samples are approached by characterizing their long-term dark current and photocurrent under X-ray incidence. It is shown how both the dark current and the sensitivity of the detectors follow similar trends at short-circuit (V = 0 V) after biasing. By performing drift-diffusion numerical simulations, it is revealed how large ionic-related built-in fields not only produce relaxations to equilibrium lasting up to tens of hours but also continue to affect the charge kinetics under homogeneous low photogeneration rates. Furthermore, a method is suggested for estimating the ionic mobility and concentration by analyzing the initial current at short-circuit and the characteristic diffusion times.